2004
DOI: 10.1021/tx034209c
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of S-(N,N-Dialkylaminocarbonyl)cysteine Adducts and Enzyme Inhibition Produced by Thiocarbamate Herbicides in the Rat

Abstract: Thiocarbamates are a major class of herbicides used extensively in the agricultural industry. It has been shown that thiocarbamates can form reactive sulfoxide and sulfone intermediates, which may be involved in the toxicity of thiocarbamates through covalent modification of cysteine and serine active sites of enzymes. Molinate has been shown to generate an S-hexahydro-1H-azepine-1-carbonyl adduct on the Cys-125 residue of the beta2- and beta3-chains of rat globin analogous to that reported for disulfiram and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 27 publications
(50 reference statements)
0
28
0
Order By: Relevance
“…There have also been a couple in vivo studies assessing ALDH activity. One study found liver ALDH inhibition in mice dosed ip with molinate (13), and the other found inhibition of ALDHs from the brain, liver, and testicle in rats dosed with molinate (10). These studies all indicate molinate or a metabolite is capable of inhibiting ALDHs, but the rates of this inhibition and the metabolite responsible for it are not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have also been a couple in vivo studies assessing ALDH activity. One study found liver ALDH inhibition in mice dosed ip with molinate (13), and the other found inhibition of ALDHs from the brain, liver, and testicle in rats dosed with molinate (10). These studies all indicate molinate or a metabolite is capable of inhibiting ALDHs, but the rates of this inhibition and the metabolite responsible for it are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…In mice dosed with molinate, peripheral nerve demyelination was observed in addition to eosinophilic bodies (swollen, degenerated axons) in the medulla and spinal cord, hindlimb adduction, splayed hindlimbs, and ataxia (7, 9). It should be noted that no peripheral neuropathy was observed in rats dosed with molinate (10). …”
Section: Introductionmentioning
confidence: 92%
“…EPA 2006). Toxicity occurs through the byproducts of EPTC metabolism, which inhibit the enzymatic activities of aldehyde dehydrogenase and cholinesterase (Smulders et al 2003, 2004; Staub et al 1995; Zimmerman et al 2004). …”
mentioning
confidence: 99%
“…A previous study has demonstrated adduct formation of molinate sulfoxide with blood proteins. (Zimmerman et al, 2004). For the oral model the fecal excretion constant (Kf) (expressed as a fraction of dose and assumed to be unmetabolized parent compound) was taken from Debaun et al, 1978.…”
Section: Methodsmentioning
confidence: 99%